2021
DOI: 10.1371/journal.pone.0259829
|View full text |Cite
|
Sign up to set email alerts
|

Boosting BCG with recombinant influenza A virus tuberculosis vaccines increases pulmonary T cell responses but not protection against Mycobacterium tuberculosis infection

Abstract: The current Mycobacterium bovis BCG vaccine provides inconsistent protection against pulmonary infection with Mycobacterium tuberculosis. Immunity induced by subcutaneous immunization with BCG wanes and does not promote early recruitment of T cell to the lungs after M. tuberculosis infection. Delivery of Tuberculosis (TB) vaccines to the lungs may increase and prolong immunity at the primary site of M. tuberculosis infection. Pulmonary immunization with recombinant influenza A viruses (rIAVs) expressing an imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Another study reported using recombinant influenza A viruses (rIVAs) expressing an immune-dominant M. tuberculosis CD4 + T cell epitope (PR8-p25 and X31-p25) as a booster vaccine for BCG, which increased the frequency of specific IFN-γ-secreting T cells and polyfunctional CD4 + T cells in the lungs. However, that vaccine did not significantly increase protection against M. tuberculosis . Validation of protective efficacy is a vital prerequisite for clinical trials of novel vaccines.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Another study reported using recombinant influenza A viruses (rIVAs) expressing an immune-dominant M. tuberculosis CD4 + T cell epitope (PR8-p25 and X31-p25) as a booster vaccine for BCG, which increased the frequency of specific IFN-γ-secreting T cells and polyfunctional CD4 + T cells in the lungs. However, that vaccine did not significantly increase protection against M. tuberculosis . Validation of protective efficacy is a vital prerequisite for clinical trials of novel vaccines.…”
Section: Discussionmentioning
confidence: 95%
“…However, that vaccine did not significantly increase protection against M. tuberculosis. 67 Validation of protective efficacy is a vital prerequisite for clinical trials of novel vaccines. Here, the primary splenocytes of mice in each immune group were extracted and challenged with M. tuberculosis in vitro.…”
Section: ■ Discussionmentioning
confidence: 99%